Clinical Results of Repeated Corneal Collagen Cross-linking in Progressive Keratoconus - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Purpose: To evaluate the effectiveness of repeated corneal collagen cross-linking (CXL) in eyes with progressive keratoconus after primary CXL. Methods: Twelve eyes of 10 patients who underwent repeated CXL were included in this study. All cases were treated with a second CXL when disease progression was noted. Uncorrected visual acuity, best-corrected distance visual acuity, and corneal tomography were performed before and after repeated CXL. Common risk factors for progression were recorded. Results: The mean age of the patients was 23.4 +/- 6.2 (14-34) years. Eye rubbing was detected in 6 patients. The preoperative maximum keratometry (Kmax) value was >58.0 diopters (D) in 11 eyes (62.2 +/- 4.9 D). Repeated CXL was performed with a mean interval of 19.3 months after the first CXL procedure when a disease progression of 2.3 D on average in Kmax was determined. With a mean follow-up of 36 months, Kmax regressed in 8 eyes, remained stable in 2 eyes, and progressed in 2 eyes after repeated CXL. Uncorrected and corrected visual acuity remained unchanged. No complications were observed. Conclusions: Repeated CXL seems to be effective in stabilizing keratoconus progression after failure of primary CXL. Patients should be followed up at least for 2 years after primary CXL.
Keywords: keratoconus; progression; repeated corneal collagen crosslinking; ULTRAVIOLET-A LIGHT; RIBOFLAVIN